(untitled) (Veterinary Science, 2017)
The causal agent of hidatidosis in our country is the tapeworm Echinococcus granulosus. This parasite takes canids as definitive host and ruminants, pigs, wild species and man as intermediate hosts. All organs with lesions suspicious for hydatid disease are seized and removed in slaughterhouses. This provides important data to understand the disease, its prevalence and distribution, to evaluate the control and eradication plans and evaluate new diagnostic techniques and treatment. There are two critical points for the diagnosis: those organs in which metacestodes are present but not macroscopically visible and those who are seized by submitting hydatid like lesions but different etiology. The latter aspect is studied considering as hypothesis an absolute lack of relationship between the macroscopic and microscopic diagnoses. The organs with macroscopic lesions were referred to the laboratory, the samples were selected, they were characterized morphologically, topographically and were processed by routine techniques for paraffin embedding and staining with hematoxylin and eosin. The positive histopathological diagnosis was based on observation of the morphology of the cysts. Of a total of 105 samples diagnosed as hydatid disease, 15 were negative by histopathological diagnosis.